MCM-41-supported platinum carbonyl cluster-derived catalysts for asymmetric and nonasymmetric hydrogenation reactions - Basu, Susmit; Mapa, Maitri; Gopinath, Chinnakonda S.; Doble, Mukesh; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2006)
Anionic platinum carbonyl Cluster ([Pt-12(CO)(24)](2-)) was ion-paired with the 3-chloropropyltrimethoxysilyl-ammonium group chemically bound to the surface of MCM-41. The materials undergo quick decarbonylation and have been characterized before decarbonylation by IR and UV-vis spectroscopy and after decarbonylation by XPS and TEM. They have been used as catalysts for the hydrogenations of methyl pyruvate, acetophenone, nitrobenzene, benzonitrile, and ethylacetoacetate. The support and the quaternary ammonium groups have significant effects on surface platinum concentration, crystallite size, and observed activity. In the hydrogenation of the prochiral substrates methyl pyruvate or acetophenone, the cinchonidine-based catalyst gives significant enantioselectivity under optimum conditions. A kinetic model that includes an enantioselective product-formation step and a hydrogen pressure-dependent step for the deactivation of the enantioselective sites gives reasonable agreement between predicted and observed enantioselectivity. The model is also in accordance with the XPS and TEM data. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: asymmetric/non-asymmetric catalysis; Enantioselectivity; functionalized MCM-41; hydrogenation catalysts; platinum carbonyl cluster

Lipases catalyzed enantioselective hydrolysis of (R,S)-methyl 1,4-benzodioxan-2-carboxylate intermediate for (S)-doxazosin mesylate - Varma, Rita; Kasture, Sangita M.; Nene, Sanjay; Kalkote, Uttam R. (World Journal of Microbiology & Biotechnology, 2008)
(S)-1,4-benzodioxan-2-carboxylic acid-1 is used as starting compound for the production of the more effective (S) enantiomer of the drug doxazosin mesylate. The catalytic ability of some commercial lipases for preparations of (S) enantiomer of 1 from (+/-) methyl 1,4-benzodioxin-2-carboxylate-2 is reported. Lipases from bacterial sources were more successful in resolving the ester than those from the yeast lipases. About 85% enantiomerically pure ester was achieved by lipase from alcaligenes sp.
Keywords: 1; 4-benzodioxan-2-carboxylate; 4-benzodioxan-2-carboxylic acid; doxazosin; Enantioselectivity; Lipases

Arthrobacter sp lipase immobilization for preparation of enantiopure masked beta-amino alcohols - Chaubey, Asha; Parshad, Rajinder; Gupta, Pankaj; Taneja, Subhash C.; Qazi, Ghulam N.; Rajan, C. R.; Ponrathnam, S. (Bioorganic & Medicinal Chemistry, 2009)
Recent reports on immobilization of lipase from Arthrobacter sp. (ABL, MTCC 5125; IIIM isolate) on insoluble polymers have shown altered properties including stability and enantioselectivity. Present work demonstrates a facile method for the preparation of enantiopure beta-amino alcohols by modulation of ABL enzyme properties via immobilization on insoluble as well as soluble supports using entrapment/covalent binding techniques. Efficacies of immobilized ABL on insoluble supports prepared from tetraethylorthosilicate/aminopropyltriethoxy silane and soluble supports derived from copolymerization of N-vinyl pyrrolidone-allylglycidyl ether (ANP type)/N-vinyl pyrrolidone-glycidyl methacrylate ( GNP type) for kinetic resolution of masked beta-amino alcohols have been studied vis-a-vis free ABL enzyme/wet cell biomass. The immobilized lipase on different insoluble/soluble supports has shown 21 - 110 mg/g protein binding and 30 - 700 U/g activity for hydrolyzing tributyrin substrate. The findings have shown a significant enhancement in enantioselectivity (ee 99%) vis-a-vis wet cell biomass providing ee 70-90% for resolution of beta-amino alcohols. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Arthrobacter sp lipase; beta-Aminoalcohol; Enantioselectivity; Immobilization; soluble polymer

Enantioselective synthesis of (+)-alpha-conhydrine and (-)-sedamine by L-proline-catalysed alpha-aminooxylation - Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (European Journal of Organic Chemistry, 2010)
An efficient organocatalytic approach to the enantioslective synthesis of two important piperidine alkaloids, namely (+)-alpha-conhydrine (98% ee) and (-)-sedamine (95% ee), by L-proline-catalysed alpha-aminooxylation of aldehydes has been developed. The strategy involves an intramolecular cyclization to construct the piperidine core.
Keywords: alkaloids; Amino acids; Aminooxylation; Enantioselectivity; organocatalysis

Immobilization of enantioselective lipase on soluble supports for kinetic resolution of drug intermediates - Chaubey, Asha; Parshad, Rajinder; Taneja, Subhash C.; Deokar, Sarika Babasaheb; Raman, Rajan C.; Ponrathnam, Surendra (Journal of Bioactive and Compatible Polymers, 2012)
The microbial lipase, Arthrobacter sp. lipase (MTCC 5125), from the Indian Institute of Integrative Medicine repository, is known as an effective catalyst for high enantioselective kinetic resolution of drug intermediates. The ABL was immobilized on water-soluble linear supports by covalently binding it to the epoxy groups on the N-vinyl pyrrolidone/allyl glycidyl ether and N-vinyl pyrrolidone/glycidyl methacrylate copolymers. The immobilized lipase, on different soluble supports, had 90-110 mg/g protein binding and 500-700 U/g hydrolysis activities for tributyrin substrate. These copolymers had soluble/insoluble characteristics in different pH ranges, which is an advantage over insoluble copolymers. A soluble polymer at neutral pH provided better accessibility to the immobilized enzyme, which was recovered by precipitation at pH 2-3 for reuse. Kinetic resolution of racemic acyl derivatives of chiral auxiliaries and drug intermediates, namely, phenyl ethanol, aminoalcohol, and fluoxetine intermediate resulted in a significant enhancement in enantioselectivity (99%).
Keywords: Arthrobacter sp lipase; Enantioselectivity; Immobilization; Kinetic resolution; N-vinylpyrrolidone; soluble polymer

Croncise organocatalytic route to protected (2S, 4R)-4-hydroxyornithine and(+)-pseudohygroline - Jha, Vishwajeet; Kumar, Pradeep (Synlett, 2014)
A practical, efficient, and organocatalytic approach to the synthesis of (2S,4R)-4-hydroxyornithine and (+)-pseudohygroline is reported using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and Horner-Wadsworth-Emmons olefination reaction of an aldehyde as the key step.
Keywords: aldehydes; Amination; Amino alcohols; cyclization; Enantioselectivity; Wittig reaction

Concise enantioselective synthesis of naturally active (S)-3-hydroxypiperidine - Dey, Soumen; Karabal, Pratibha U.; Sudalai, Arumugam (Synthetic Communications, 2015)
A short and efficient enantioselective synthesis of natural product (S)-3-hydroxypiperidine has been achieved starting from commercially available raw materials employing two catalytic routes: (i) cocatalyzed hydrolytic kinetic resolution (HKR) of racemic methyl-3-(oxiran-2-yl)propanoate; (ii) proline-catalyzed -aminooxylation followed by Horner-Wardsworth-Emmons olefination in high enantiomeric purity (97% ee) and high overall yield (38%).
Keywords: Asymmetric synthesis; bioactivity; Enantioselectivity; Natural products; organocatalysis

First enantioselective synthesis of surinamensinol B and a non-natural polysphorin analogue by a two-stereocentered hydrolytic kinetic resolution - Lalwani, Komal G.; Sudalai, Arumugam (European Journal of Organic Chemistry, 2015)
An efficient and economical approach to the synthesis of antitumor and anti-inflammatory surinamensinol B (1) and antimalarial polysphorin analogue 2 has been achieved with high enantiomeric purity (96% ee) by starting from commercially available 3,4,5-trimethoxybenzaldehyde. The key steps of the strategy include a Co-catalyzed two-stereocentered hydrolytic kinetic resolution (HKR) of racemic 2[( methoxymethoxy)(3,4,5-trimethoxyphenyl)methyl] oxirane (13) as the chiral inducing step followed by a Mitsunobu reaction. Chiral epoxide 14 and chiral diol 15 were utilized in the syntheses of both compounds.
Keywords: Biological activity; Enantioselectivity; Kinetic resolution; Natural products; Total synthesis

Proline-catalyzed alpha-aminooxylation of beta-amino aldehydes: access to enantiomerically pure syn- and anti-3-amino-3-aryl-1,2-alkanediols - Venkataramasubramanian, V.; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Synlett, 2015)
A new synthetic method for enantioselective synthesis of syn 3-amino-3-aryl-1,2-alkanediols via praline catalyzed alpha-aminaoxn y ylation of beta-amino aldehydes des are described. This methodology is successfully applied to a concise and protecting group-free asymmetric synthesis of (-)-cytoxazone (+)-epi-cytoxazone and formal synthesis of N-thiolated 2-oxazolidinone.
Keywords: amino aldehydes; Asymmetric synthesis; catalysis; diastereoselectivity; Enantioselectivity; Natural product

Robustness screen in enantioselective catalysis enabled generation of enantioenriched heterocyclic scaffolds in one pot - Bagle, Pradip N.; Shinde, Valmik S.; Patil, Nitin T. (Chemistry-A European Journal, 2015)
Enantioselective catalysis has emerged as a powerful synthetic paradigm and has accelerated the development of new methods to make diverse chiral molecules. Generally, these reactions are very sensitive to the steric and electronic environment present in the catalyst as well as the substrates. With this scenario, the presence of an additional component in the reaction mixture is expected to add complexity in achieving the enantioselective variants. Herein, we report that various enantioenriched molecules could be obtained from multiple starting materials in one pot. The reaction of aminoaromatics A with alkynols B-1, B-2, B-3...B-n with a Au-I/chiral BrOnsted acid catalyst afforded AB(1)*, AB(2)*, AB(3)*...AB(n)*; while, the reaction of alkynols B with aminoaromatics A(1), A(2), A(3)...A(n) under the same reaction conditions gave A(1)B*, A(2)B*, A(3)B*...A(n)B*.
Keywords: chiral Bronsted acid; Enantioselectivity; Gold; molecular scaffolds; robustness screen

Organocatalytic asymmetric cascade reaction of gamma-substituted deconjugated butenolides with o-formyl-beta-nitrostyrene - Deepake, Siddharth K.; Lanjewar, Atul B.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2018)
An efficient chemo-, diastereo- and enantio-selective cascade synthesis of functionalized indanols bearing four contiguous stereogenic centres has been developed via the reaction of beta,gamma-butenolides with o-formyl-beta-nitrostyrenes in the presence of bi-functional hydrogen-bonding catalyst. Indanol derivatives containing gamma,gamma-disubstituted butenolides were obtained in good yields and with moderate to high enantioselectivities/diastereoselectivities.
Keywords: butenolides; Cascade reaction; Enantioselectivity; Indanol; organocatalysis

Concise formal synthesis of (-)-(6R,11R,14R)-colletallol via D-proline catalysed alpha-aminooxylation-Wittig olefination strategy - Dey, Soumen; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient enantioselective formal synthesis of marine macrolide (-)-(6R,11R,14R)-colletallol has been achieved starting from commercially available raw materials. The key reactions include the D-proline catalyzed a-aminooxylation of aldehyde followed by Horner-Wardsworth-Emmons olefination in a sequential fashion to give the macrolide key intermediate 5 in high enantiomeric purity (97% ee) and high overall yield (32%).
Keywords: alpha-aminoxylation; Asymmetric synthesis; Enantioselectivity; Natural products; organocatalysis

"Weak" C-H•••S interaction drives enantioselectivity in cinchona alkaloid complex catalyzed thiocyanation - Banerjee, Subhrashis; Vanka, Kumar (Chemistry-An Asian Journal, 2023)
The great success of asymmetric organocatalysis has made it one of the most important advancements made in chemistry in the past two decades. A significant achievement in this context is the asymmetric organocatalysis of the thiocyanation reaction. In the current study, computational studies with density functional theory have been done in order to understand an interesting experimental finding: the reversal of enantioselectivity from R to S when the electrophile is changed from beta-keto ester to oxindole for the thiocyanation reaction with the cinchona alkaloid complex catalyst. The calculations reveal an unusual fact - the principal reason for the reversal is the presence of the C-H center dot center dot center dot S noncovalent interaction, which is present only in the major transition states in each of the two nucleophile cases. Only recently has it been realized that the supposedly weak C-H center dot center dot center dot S noncovalent interaction has the properties of a hydrogen bond, and the fact that this interaction is the cause of enantioselectivity has relevance, because of the large number of asymmetric transformations involving the sulphur heteroatom.
Keywords: Density functional calculations; Enantioselectivity; noncovalent interactions; organocatalysis; reaction mechanisms

Organocatalytic route to the enantioselective synthesis of syn/ anti-α-hydrazino-γ-fluoro alcohols - Khonde, Nilesh S.; Said, Madhukar S.; Danve, Shivam S.; Kumar, Pradeep (Tetrahedron Letters, 2024)
A general organocatalytic method has been developed for the asymmetric synthesis of alpha-hydrazino-gamma-fluoro alcohols, a precursor to syn/anti-1,3-fluoro amines. The strategy employs alpha-fluorination catalyzed by prolinederived catalyst, (S)-alpha,alpha-bis[3,5-bis(trifluoromethyl)phenyl]-2-pyrrolidinemetha nol trimethylsilyl ether followed by Horner-Wadsworth-Emmons (HWE) olefination of aldehydes, and proline-catalyzed alpha-amination as the key steps. The title compounds showed excellent diastereoselectivity (up to 99:1) and enantioselectivity (up to 99 %).
Keywords: alpha-Amination; alpha-Fluorination; diastereoselectivity; Enantioselectivity; HWE olefination; organocatalyst

Structure of epoxide hydrolase 2 from Mangifera indica throws light on the substrate specificity determinants of plant epoxide hydrolases - Bhoite, Ashwini; Gaur, Neeraj K.; Palange, Megha; Kontham, Ravindar; Gupta, Vidya; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2024)
Epoxide hydrolases (EHs) are a group of ubiquitous enzymes that catalyze hydrolysis of chemically reactive epoxides to yield corresponding dihydrodiols. Despite extensive studies on EHs from different clades, generic rules governing their substrate specificity determinants have remained elusive. Here, we present structural, biochemical and molecular dynamics simulation studies on MiEH2, a plant epoxide hydrolase from Mangifera indica. Comparative structure-function analysis of nine homologs of MiEH2, which include a few AlphaFold structural models, show that the two conserved tyrosines (MiEH2Y152 and MiEH2Y232) from the lid domain dissect substrate binding tunnel into two halves, forming substrate-binding-pocket one (BP1) and two (BP2). This compartmentalization offers diverse binding modes to their substrates, as exemplified by the binding of smaller aromatic substrates, such as styrene oxide (SO). Docking and molecular dynamics simulations reveal that the linear epoxy fatty acid substrates predominantly occupy BP1, while the aromatic substrates can bind to either BP1 or BP2. Furthermore, SO preferentially binds to BP2, by stacking against catalytically important histidine (MiEH2H297) with the conserved lid tyrosines engaging its epoxide oxygen. Residue (MiEH2L263) next to the catalytic aspartate (MiEH2D262) modulates substrate binding modes. Thus, the divergent binding modes correlate with the differential affinities of the EHs for their substrates. Furthermore, long-range dynamical coupling between the lid and core domains critically influences substrate enantioselectivity in plant EHs.
Keywords: Enantioselectivity; Epoxide hydrolase; molecular dynamics simulation; Regioselectivity; X-ray crystallography